Subnotificação de Acidente de Trabalho Fatal: um estudo de caso no município de Uberlândia - Silva, Gisella Garcia da (2017)
Workplace accidents are becoming more prevalent all over the world, especially in emerging countries, as is the case in Brazil. Fatal occupational accidents are the ones that generate greater concern among scholars and workers in general, given the social and financial costs, both for the worker who is the victim of the accident and for the family. Knowing the magnitude of fatal work accidents in Brazil is of paramount importance for planning actions aimed at minimizing them, especially accidents due to external causes, which are the most difficult to measure, given their characteristics and to involve Both formal and informal workers. In this sense, it is a peaceful point in the literature that the sources responsible for the measurement of fatal work accidents, among which the Mortality Information System (SIM) and the Work Accident Communication (CAT), present several shortcomings with regard to Death record This contributes to the underreporting of fatal work accidents in the economically active population, with negative consequences in the planning of health actions for workers. The objective of the present study was to analyze the epidemiological profile of deaths due to external causes, occurring among the population of productive age in the city of Uberlândia, located in the State of Minas Gerais, and to identify whether there is a real underreporting of occupational accidents Fatal The methodological course used was the analysis of the Death Certificates (DO) in the period of 2015, motivated by external causes, between the age group of 15 to 64 years of age, as well as the Mortality Information System (SIM) and the Bulletin Epidemiological of Mortality, administered by the Epidemiological Surveillance of the Municipal Health Department. It is concluded by means of this analysis that the hypotheses initially raised are correct, that is, it was observed inadequacy and failures to fill Dos, especially in relation to external causes , And the underreporting of fatal work accidents due to external causes. In this sense, it confirms in this specific study what has already been reported in other studies on the problem of underreporting.